Is serum apelin related to portal hemodynamics in patients with liver cirrhosis? - Ashraf G Dala; Osama M Ebied; Gamal Y Abo-Raia (SpringerOpen, 2018)
Background Apelin is the endogenous ligand of the angiotensin-like receptor. The expression of apelin-APJ (apelin receptor) signaling is associated with the development of portal hypertension (PH) and contributes toward the formation of Porto systemic collaterals and splanchnic neovascularization in PH. Aims We aimed to study the relationship between apelin and portal hemodynamics in cirrhotic patients. Patients and methods Thus study included 60 cirrhotic patients from Menoufia University Hospitals (Egypt) and 20 healthy volunteers as a control group. Participants underwent a physical examination and laboratory investigations [complete blood count, urea, creatinine, alanine transaminase, aspartate transaminase (AST), serum albumin, bilirubin, international normalized ratio, hepatitis C virus antibody, hepatitis B virus antigen, hepatitis C virus PCR, alpha feto protein (AFP), and serum level of apelin]. Abdominal ultrasonographic studies of portal vein diameter, splenic size, and portal hemodynamics were carried out for all participants. Child-Pugh score, model for end-stage liver disease score, and AST/platelet (PLT) index were calculated for all participants. Results Serum apelin was highly significantly elevated in cirrhotics than in controls, with a P value of 0.001. Serum apelin was significantly correlated to some laboratory parameters in cirrhotics such as PLT count, alanine transaminase, AST, γ-glutamyl transferase, and bilirubin, with P value less than 0.05. There was a positive correlation between serum apelin level and the degree of liver fibrosis estimated by the AST/PLT index. Serum apelin was significantly correlated to portal vein diameter and portal flow velocity, with a P value less than 0.05, and highly significantly correlated to splenomegaly, with a P value of 0.001. The optimal cut-off point of serum apelin for the prediction of PH in cirrhotics is 2550 ng/dl, with a sensitivity of 89%, a specificity of 65%, and an accuracy of 81%. Conclusion Serum apelin is elevated in patients with cirrhosis and PH, and a positive correlation is found between serum apelin and the degree of hepatic fibrosis. Measurement of serum apelin represents a rapid, noninvasive method for the prediction of PH in cirrhotics and can assess the degree of hepatic fibrosis.